OPTIMIZATION ENTREPRENEURSHIP ORIENTATION IN CREATING ADDED VALUE OF PASAMAN CITRUS - Mega Usvita (Jurnal Apresiasi Ekonomi, 2019)
West Pasaman is an area rich in agricultural products. One of the region's agricultural products is Citrus, which are popularly known as Pasaman Citrus. Pasaman Citrus has a sweet taste and has a lot of vitamin content. Pasaman Citrus Market is already so extensive. This Citrus has been sold in other regions. To increase added value, bring ideas to developing products such as packaged orange juice, syrup and other products. This idea will certainly increase the marketing and income of citrus producers. The research method is descriptive qualitative which is explored from three dimensions of entrepreneurship, namely innovation, where citrus producers are able to create new products that can later expand market opportunities. Furthermore proactive spirit, where the development of these products will increase competitiveness in the market and will get opportunities both from the local market and the market in several other regions. Then the courage to take risks. With the increasing competition, citrus producers are also able to deal with risks and minimize the risks. Keyword: Innovation, proactive spirit, Courage to take risks